Investigation on the Subcooled Boiling in Vertical Pipe With Uncertainties From Boundary Conditions by Using FLUENT - Zhang, Xiang; Zhang, Rui; Lv, Xindi; Cong, Tenglong (Frontiers in Energy Research, 2018)
Subcooled boiling flow taking place in the reactor system plays a critical role in the safety of nuclear power plants. It has been studied by experiments and system codes in the past decades. Now subcooled boiling can be predicted with CFD code based on the Eulerian two-fluid model, with the development in the computational technology and the understanding in the mechanism of two-phase flow. The published works on the validation of CFD code for two-phase flow were carried out based on the deterministic analysis by comparing the calculated and experimental nominal inputs and outputs, which is not sufficient for code validation since it didn't consider the inevitable uncertainty in the experiment measurements. In the current work, subcooled boiling was predicted by using a CFD code, FLUENT, with consideration of the uncertainties of boundary conditions. The resultant parameters with uncertainties were compared to the experiment data for validation purpose. Confidence intervals of the two-phase parameters were predicted. Besides, correlations between the boundary conditions and the outputs were analyzed.